Defining morality, applying standards and shaping attitudes: replies to Copson, Hobbs and Kotzee. Issue 2 (2nd April 2020) - Hand, Michael
ABSTRACT: In the preceding articles, Andrew Copson, Angie Hobbs and Ben Kotzee make a number of interesting criticisms of my book, A Theory of Moral Education. Here I offer some replies.